2007
DOI: 10.1182/blood-2007-02-074203
|View full text |Cite
|
Sign up to set email alerts
|

Novel RUNX1 isoforms determine the fate of acute myeloid leukemia cells by controlling CD56 expression

Abstract: CD56 high acute myeloid leukemias (AMLs) have a poor prognosis, but it has been unclear how CD56 expression is controlled and how it relates to clinical aggressiveness. We show that CD56 expression on AML cells correlates with an abnormal expression pattern of runtrelated transcription factor 1 (RUNX1) isoforms. Whereas full-length p48 RUNX1 (p48) up-regulated CD56 in AML cells, 3 previously unknown shorter RUNX1 isoforms, p38a, p30, and p24, suppressed CD56 expression. Both p48 and CD56 induced nuclear transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Runx1, also known as acute myeloid leukemia-1, is significantly upregulated in several types of leukemia (Asou, 2003;Gattenloehner et al, 2007) as well as in breast cancer (Cancer Genome Atlas Network, 2012). Additionally, Runx1 upregulation is associated with progression of G1/S during cell cycle (Bernardin-Fried et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Runx1, also known as acute myeloid leukemia-1, is significantly upregulated in several types of leukemia (Asou, 2003;Gattenloehner et al, 2007) as well as in breast cancer (Cancer Genome Atlas Network, 2012). Additionally, Runx1 upregulation is associated with progression of G1/S during cell cycle (Bernardin-Fried et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…27,28 In an attempt to identify potential factors that could regulate PRC2-mediated suppression, we analyzed the CTNNA1 promoter 5.0 kb upstream of the transcriptional start site and found potential binding sites for 4 transcription factors (AML-1, MZF-1, NF-Y, and C/EBP␣) that have previously been shown to contribute to myeloid development and self-renewal and transformation of HSCs [29][30][31] ( Figure 1A). Neither knockdown of AML-1 and MZF-1 using retrovirally mediated shRNA 32 nor suppression of heterotrimeric NF-Y function through retrovirally mediated overexpression of NF-Ya m29 (a dominant-negative form containing a mutation in the DNA-binding domain) 31 ChIP assays using specific antibodies directed against the C-terminus (C1 and C2) or the N-terminus of C/EBP␣ (N) revealed that only p30 C/EBP␣, but not p42 C/EBP␣, was specifically associated with the P1 and P1E1 regions of the CTNNA1 promoter solely in HL-60 cells ( Figure 3A lanes 2 and 3). This unanticipated finding suggests a lack of functional p42 C/EBP␣ protein in HL-60 cells.…”
Section: The Ratio Of P42 Versus P30 C/ebp␣ Is Critical For Prc2 Recrmentioning
confidence: 99%
“…30 Slides were viewed with equipment from Olympus (Hamburg, Germany; camera BX50/DP-Soft version 5) and processed with Adobe Photoshop version 3.0 (Adobe Systems, San Jose, CA). The anti-phospho-Akt antibody used was from Cell Signaling Technology (no.…”
Section: Histochemical Analysismentioning
confidence: 99%